PENATALAKSANAAN FISIOTERAPI PADA KASUS BRONKIEKTASIS DENGAN MODALITAS NEBULIZER, INFRARED (IR), POSTURAL DRAINASE DAN ACTIVE CYCLE BREATHING TECHNIQUE (ACBT) - Septiana Arifadhi; Ade Irma Nahdliyyah; Fatonah Sulistyowati (SINERGI : Jurnal Riset Ilmiah, 2026)
Background Breathing is an automatic activity in various daily activities, but in patients with lung disorders such as bronchiectasis, this function becomes difficult due to several factors. This is evidenced by data in the RSUP area showing an increase in the number of patients reaching 2,836 cases per year in 2025. The purpose of this study was to determine the effect of physiotherapy management in cases of Bronchiectasis with the modalities of Nebulizer, Infrared, Postural Drainage and Active Cycle Breathing Technique (ACBT). The study was conducted using a descriptive analytical method in the condition of Bronchiectasis during 3 interventions. The method of data collection and data analysis was by autoanamnesis. The research instruments were sputum examination with auscultation, spasm with palpation, chest pain and cough with a VAS scale, shortness of breath with a borg scale instrument, thoracic cage expansion with a midline and functional activity with TUGT and London Chest ADL. Results: (1) There was a reduction in the amount of sputum from T1= 2 to T3= 1. (2) There was a decrease in spasm in the left upper trapezius muscle from T1= 1 to T3= 0. (3) There was a decrease in the value of chest pain from T1= 4 cm to and T3= 2 cm. (4) There was a decrease in the degree of shortness of breath from T1= 4 to T3= 3 (5) There was a decrease in the frequency of coughing from T1= 3 to T3= 2 (6) There was an increase in thoracic cage expansion from T1 at Axila= 2 cm, ICS 4-5= 1 cm, proc. Xypoideus= 1.5 cm to T3 at Axila= 3 cm, ICS 4-5= 2 cm, proc. Xypoideus = 2 cm (7) There is an increase in functional activity seen from the TUGT and London Chest Activity of Daily Living scores. The TUGT results were obtained from T1 = 14 seconds to T3 = 11.5 seconds and the London Chest ADL results from T1 = 21 to T3 = 19. The conclusion is that physiotherapy management with the Nebulizer, Infrared, Postural Drainage and Active Cycle Breathing Technique (ACBT) modalities can reduce the problems that exist in patients with Bronchiectasis.